ACRÉSCIMOS CONSTRUTIVOS NOS CONDOMÍNIOS FECHADOS - Zorzal, Anny Keller Helmer; Rodrigues, Edna Aparecida Nico; Bissoli-dalvi, Márcia (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
As the proliferation of closed condominiums is directly linked to the phenomenon of globalization of the economy and its effects on society, it has become popular, and much of the city is being defined by closed residential settlements, adopting particularly defined deployments, morphologies and typologies, where little or no attention has been given to compliance with environmental laws among municipalities, landowners and the Public Prosecutor's Office. In this context, the objective of this article was to analyze the constructive additions that the closed condominiums allow through the Convention, which demonstrate that they ignore the urban planning indexes foreseen in the municipal and federal norms. The methodology took place in three stages: choice of study object, survey and study of legislation and analysis of results. The results obtained showed that there were no clear recommendations or guidelines in the condominium convention related to the passive strategies: permanent ventilation, natural lighting and shading, mentioned in NBR 15220 (ABNT, 2003): Thermal performance of buildings.